The Endhog-Endhogan Tradition in the Perspective of Islamic Education: A Study of Local Wisdom in the Banyuwangi Community - Icha Mutiara Safa (Research Departement of Darullughah Wadda'wah International Islamic University Bangil, Pasuruan, 2026)
The Endhog-Endhogan tradition is one form of local wisdom practiced by the Muslim community in the Banyuwangi region of East Java to commemorate the birthday of the Prophet Muhammad SAW. This tradition is not only an integral part of the local community’s culture, but it also holds religious significance and embodies the values of Islamic education. This study aims to examine the meaning and values of Islamic education embedded within the Endhog-Endhogan tradition as a form of local wisdom among the Banyuwangi community. Endhog-Endhogan is a tradition practiced by the Muslim community in Banyuwangi to commemorate the birth of the Prophet Muhammad (Maulid Nabi Muhammad SAW). Through a qualitative approach employing field study and descriptive analysis methods, this research reveals that the tradition not only serves social and cultural functions but also contains Islamic educational values such as exemplary conduct, mutual cooperation (gotong royong), gratitude, and expressions of love for the Prophet Muhammad (peace be upon him). These values align with the principles of Islamic education, which emphasize the cultivation of noble character, the strengthening of faith, and the development of socio-religious character among learners. Hence, Endhog-Endhogan can be understood as a tradition that integrates Islamic teachings with local culture. The results of this study also aim to describe the sequence of the Endhog-Endhogan ritual and to explore the process of Islamization within this tradition as it has developed among the people of Banyuwangi.